P79 Multicenter assessment of the Tigertriever 13 for thrombectomy in primary medium vessels occlusions. (29th August 2022) - Guenego, A; Lubicz, B; Dmytriw, A; Regenhardt, R; Diestro, J; Jabbour, P; Siegler, J; Gonzalez, N; Levitt, M; Tancredi, I; Rouchaud, A; Fiehler, J; et al.
Abstract : Introduction and Aim of the Study: To evaluate the safety and efficacy of the Tigertriever 13 1, 2 (Rapid Medical, Yoqneam, Israel) stent-retriever in acute ischemic stroke (AIS) patients with a primary medium vessel occlusion (MeVO). 3 Methods: A retrospective review of the DMVO Consortium, a synthesis of prospectively maintained databases at XX academic institutions in North America, Asia, and Europe, was performed to analyze consecutive AIS patients who underwent thrombectomy with the Tigertriever 13 for a primary MeVO. Patients' characteristics, procedural complications, angiographic and clinical outcomes were reviewed. Results: Between January 2017 and January 2022, 58 patients and MeVO were included (53% female, median age 77 [63–83] years, 50% of IVtPA before thrombectomy). The Tigertriever13 was used in 46/58 (79%, ) as a first-line stentretriever and in 12/58 (21%) as a rescue-therapy after failure of another technique. Overall, the successful reperfusion rate (mTICI 2b, 2c, 3) was 93% for the dedicated vessel. The first-pass effect was of 15/46 (33%) in the first-line Tigertriever group. At day 1, control imaging showed a subarachnoid-hemorrhage in 33%, a parenchymal hematoma in 9%, and a symptomatic intracranial hemorrhage (≥4 deterioration in NIHSS) in 3/58 (5%). At 3 months, 61% of the patients (33/58) had a favorable outcome (mRS 0–2). Conclusion: Mechanical thrombectomy using the Tigertriever 13 appears to be safe and effective for MeVO among different centers and physicians, as a first-line device or as a recue-therapy after an other approach failure. References: Guenego A, Mine B, Bonnet T, et al . Thrombectomy for distal medium vessel occlusion with a new generation of stentretriever (tigertriever 13). Interv Neuroradiol 2021: 15910199211039926. 2021/09/14. DOI: 10.1177/15910199211039926. Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: Consultancy for Rapid Medical (travel grant only)